2017
DOI: 10.1111/jocn.13859
|View full text |Cite
|
Sign up to set email alerts
|

Nursing students’ preferences for clinical placements in the residential aged care setting

Abstract: Aims and objectives: To examine nursing student placement preferences submitted as online comments to a university's placement management system, to inform strategies for positive residential aged care experiences.Background: There are predicted shortages of nurses to service an ageing popula-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 34 publications
0
11
1
Order By: Relevance
“…Differences were highlighted between subgroups of students, with older students and those from a migrant background being more likely to choose to work in the sector. In an 8‐year longitudinal study of Australian nursing students’ responses for placement choices in aged care, only 17% ( n = 104) of 607 responses were related to requests for placement in aged care (Lea et al 2018). These studies indicate that students’ personal experience in the care of others and their career planning have a strong influence on their choice to work in the sector.…”
Section: Introductionmentioning
confidence: 99%
“…Differences were highlighted between subgroups of students, with older students and those from a migrant background being more likely to choose to work in the sector. In an 8‐year longitudinal study of Australian nursing students’ responses for placement choices in aged care, only 17% ( n = 104) of 607 responses were related to requests for placement in aged care (Lea et al 2018). These studies indicate that students’ personal experience in the care of others and their career planning have a strong influence on their choice to work in the sector.…”
Section: Introductionmentioning
confidence: 99%
“…[2] Clinical practice allows nursing students to develop competencies required for professional practice and transform theoretical knowledge into patient care. [3] It meets accreditation requirements, supports students' skill acquisition, [4] and ensures the ability of nursing student to practice as a nurse. [5] Hence, the quality of clinical preparation of nursing students has a great influence on the quality of the program.…”
Section: Introductionmentioning
confidence: 97%
“…However, several studies have shown that nursing homes have an ‘image problem’ among nursing students, who often conceive it as a clinical arena that offers limited learning opportunities and inadequate learning outcomes (Lea et al, 2018; van Iersel et al, 2018). Students have expressed a need for more support and mentoring during nursing home practice to improve their practice outcomes and receive help in developing critical thinking about patient situations in nursing homes (Bjørk et al, 2014).…”
Section: Introductionmentioning
confidence: 99%